Identifikasi dan Karakterisasi Bakteri Asam Laktat Isolat Susu Segar Sapi Bali (IDENTIFICATION AND CHARACTERIZATION OF LACTIC ACID BACTERIA ISOLATED FROM BALI CATTLE’S RAW MILK) - Sujaya, I Nengah; Nocianitri, Komang Ayu; Aryantini, Ni Putu Desy; Nursini, Wayan; Ramona, Yan; Orikasa, Yoshitake; Kenji, Fukuda; Urashima, Tadashu; Oda, Yuji (Jurnal Veteriner; Vol 17 No 2 (2016), 2016)
Bali cattle is an indigenous spesies in Bali, which pay great attention due to its uniqueness. Numerousarticles have been published on Bali cattle especially related to its disease, nutritional requirement forgrowth and domestication. Nevertherless, it was no any report has been published on the lactic acidbacteria (LAB) assosiated with the cattles raw milk and its potential used as probiotic. This work isaimed to identify LAB isolated from bali cattle raw milk and its resistance to secondary bile acid (sodiumdeoxy cholic), a prequisite in development of probiotic for human. The results revealed that based upon thehomology studies of the variable region I, II, and III sequences of the 16S rDNA showed that 44 out of 62isolates were closely related to Pediococcus acidilactici; 11 out of 62 isolats were closely related to Enterococusgallinarum, five out of 62 isolates were closely related to Lactococcus garvieae, while only one isolate was closely related to Lactobacillus plantarum and Weisella confusa. Some isolates showed resistant to 0.2-0.6mM deoxy cholic acid, which might be also resist in human gastrointestinal tract conditions. Based onthose finding, it can be concluded that the LAB associated with raw bali cattle milk were closey related toP. acidilactici, E. gallinarum, Lac. garvieae, Lb. plantarum and W. confusa, which different from thosecommonly LAB found in others cattle raw milk. Somes isolates were potential to be developed as probioticfrom human helath.
Keywords: Bali cattle milk, lactic acid bacteria, 16S rDNA, probiotic